Extreme rainfall in East Africa, October 2019–January 2020 and context under future climate change. (16th August 2020) - Wainwright, Caroline M.; Finney, Declan L.; Kilavi, Mary; Black, Emily; Marsham, John H.
Abstract : The 2019 October–December rains over East Africa were one of the wettest seasons on record, with many locations receiving more than double the climatological rainfall, leading to floods and landslides. The wet conditions were associated with the positive Indian Ocean Dipole event, with warm sea surface temperatures in the western Indian Ocean. Seasonal forecasts correctly predicted above average rainfall during the season. Climate model projections suggest that such events may become more frequent under future climate change.